Earnings management and European Regulation 1606/2002: Evidence from non-financial Portuguese companies listed in Euronext - Agostinho Pereira; Maria do Céu Gaspar Alves (Revista de Contabilidad: Spanish Accounting Review, 2017)
Background Since 2005, Portuguese listed companies have experienced an important institutional change, the mandatory adoption of new accounting standards (IFRS/IAS). European Union Regulation 1606/2002 made compliance with IFRS mandatory for the consolidated accounts of companies with securities traded on a regulated market. Existing literature suggests that accounting standards and country-specific characteristics affect the level of earnings management.